PENGARUH PUBLIC GOVERNANCE TERHADAP KUALITAS KINERJA - NUNUNG NURUL HIDAYAH (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2004)
Public accountability, transparency, and the effectiveness of human resources management should be enhance to reform public sector institutions. This study examined the difference between the degree of importance and implementation of public governance and performance quality. This study also investigated public governance variables, which are predicted to have effects on performance quality. Variables in this research are accountability, transparency, and the effectiveness of human resources management. The result concluded the differences between the degree of importance and implementation of public governance and performance quality. The implementation of public governance and performance quality are lower than the degree of importance. The result also showed that only the effectiveness of human resource management which had effect on performance quality.